(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2004)
Possibility of using thin layers of natural sorbent ion-exchanger argyllizite for quantitative determination of vanadium in solutions has been studied. When using hydrochloric acid (0.l mol /l)–ethanol 9:1 by volume mixtures as mobile phase the spots of vanadate-ions on the thin layer of the sorbent have compact strictly oval shape. This allows to suggest a new method for determination of micro¬quantities of vanadium the relative error of which is not more than 8–10%.